Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1093/ijnp/pyu061
|View full text |Cite
|
Sign up to set email alerts
|

Lurasidone Exerts Antidepressant Properties in the Chronic Mild Stress Model through the Regulation of Synaptic and Neuroplastic Mechanisms in the Rat Prefrontal Cortex

Abstract: Background:Major depression is associated with several alterations, including reduced neuronal plasticity and impaired synaptic function, which represent an important target of pharmacological intervention.Methods:In the present study, we have investigated the ability of the antipsychotic drug lurasidone to modulate behavioral and neuroplastic alterations in the chronic mild stress model of depression.Results:Rats that show reduced sucrose consumption after 2 weeks of chronic mild stress have reduced expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
57
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 56 publications
(67 citation statements)
references
References 57 publications
10
57
0
Order By: Relevance
“…Moreover, we have recently reported that the ability of lurasidone to normalize the anhedonic-like phenotype induced by CMS may be also due to the modulation of synaptic and neuroplastic mechanisms [57].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we have recently reported that the ability of lurasidone to normalize the anhedonic-like phenotype induced by CMS may be also due to the modulation of synaptic and neuroplastic mechanisms [57].…”
Section: Discussionmentioning
confidence: 99%
“…Studies to identify the receptor subtype indicate that a selective muscarinic 1 antagonist produces antidepressant actions similar to scopolamine in rodent models 173,174 . Preclinical studies also report that other putative antidepressant agents increase or are dependent on mTORC1 signaling 175178 . Together, these studies provide additional supporting evidence that the mTORC1 dendritic translational cascade and synapse formation may represent a common final pathway for a wide range of rapid acting, efficacious antidepressants.…”
Section: Novel Targets For Rapid Acting Antidepressantsmentioning
confidence: 99%
“…We have previously shown that CMS is able to induce depressive-like behaviors such as anhedonia (Rossetti et al, 2016) as well as cognitive impairment (Calabrese et al, 2017), which are associated with alterations in key molecular players for psychiatric disorders (Luoni et al, 2014; Calabrese et al, 2016b; Molteni et al, 2016). We also investigated the effect of a chronic treatment with lurasidone in counteracting the CMS-induced alterations in rat hippocampus.…”
Section: Introductionmentioning
confidence: 99%